Drought-Induced Morphophysiological and Metabolite Changes in Oil Palm Seedlings from Jambi, Indonesia - Andesmora, Evan Vria; Hamim; Sulistijorini; Muttaqin, Mafrikhul; Triadiati (Bogor Agricultural University, Indonesia, 2025)
Oil palm requires sufficient water for optimal growth. However, oil palm plantations in Indonesia face the challenge of global climate change, which causes increased temperatures and unpredictable rainy seasons. The research aimed to analyze oil palm accessions from Jambi that are tolerant to drought based on plant morphophysiological characteristics and metabolite profile. The experiment was conducted in the greenhouse using a factorial randomized block design. Five oil palm accessions were evaluated in this study, i.e., Muara Jambi (MJ), Tebo (TB), Tanjung Jabung Barat (TJB), Merangin (MR), and Simalungun (SM). Seedlings were planted in pots containing 20 kg of soil and acclimatized for 14 days before treatment. Drought treatments were carried out for two, four, and six weeks. Observations were made on growth, physiological, and metabolite changes at the end of each drought period. The study showed that the SM accession exhibited a higher photosynthetic rate and fresh and dry biomass than the other accessions. However, the content of proline and MDA increased significantly in oil palm throughout the drought periods. Metabolomic profiling revealed a significant increase in 13 metabolites under drought stress, i.e., citramalate, L-tyrosine, ferulate, and 3-4-dihydroxybenzoate were the four most prevalent metabolites in the leaf. The root produced more L-proline, aspartate, aconitate, kaempferol-3-o-pentoside, oxoadipate, citrate, L-phenylalanine, maltose, phenylacetic acid, and citramalate. These metabolites have roles in plant metabolic pathways such as valine, leucine, and isoleucine biosynthesis, phenylpropanoid biosynthesis, arginine and proline metabolism, citrate cycle (TCA cycle), lysine biosynthesis, phenylalanine metabolism, and starch and sucrose metabolism.